Statistical Data Analyses for Investigating Recent Major Earthquakes and Mitigating their Damages in Japan - Kawase, Yuji; Oyama, Tatsuo (International Journal of Operational Research/Nepal, 2019)
Japan has experienced many large-scale natural disasters such as earthquakes, typhoons with heavy rain and landslides, tornadoes and so on. Every time we have such serious damages due to major natural disasters, public utilities such as electricity, gas, and water have been cut off and stopped. In this paper we take four major earthquakes, which occurred very recently with serious damages. Using data such as deaths and missing people, refugees, and refugee camps, water supply suspension and its recovery and applying various statistical data analyses techniques and mathematical models, we show our findings and policy suggestions obtained from those analyses. In addition, we propose a mathematical modeling technique for quantitatively measuring the robust-ness of the water supply network system. Our approach is based upon the network flow optimization model and Monte Carlo random generation technique. We illustrate numerical results obtained from our numerical experiments.